An optimization method on managing Ranque–Hilsch vortex tube with the synergy between flow structure and performance. (June 2021) - Guo, Xiangji; Liu, Bo; Lv, Jinsheng; Zhang, Bo; Shan, Yong
Abstract: In this paper, the relationship between the flow structures in the vortex tube and its coordinated variation of the performance is numerically investigated. It is shown that the poor performance of vortex tubes is possibly due to the morbid flow structure controlling in it. A new method of managing the flow structures inside the vortex tube to achieve best suitable to the operation condition with a variable cold orifice ratio is proposed. Different cold orifice ratios, ranging from 0.3c /D<0.8, were adopted to study how the cold orifice ratio affects the performance, especially the cooling performance. An interesting and important characteristic of the operating performance of a vortex tube can be realized by continuously changing the cold orifice ratios, that is, when the cold mass fraction increasing from 0.1 to 0.9, the total temperature difference can be "monotonically decreasing" (for Dc /D ≤ 0.36), "firstly increasing then decreasing" (for 0.36c / D <0.72) or "monotonically increasing" (for Dc / D  = 0.72), which provides a useful method to control the temperature of cold/hot stream and also boosts the cooling capacity. This feature results from the better synergy between the flow structure and the operation conditions, which is also simple and easy to be realized. Besides, a fast and preliminary diagnosis method on the flow field of the main tube with the distribution of the reverse flow boundary is presented, and it is helpful to the optimization design of vortex tube.